Older persons' knowledge of HIV and AIDS prevention in a province of South Africa - Sebastiana Zimba Kalula; Tarryn Blouws (AOSIS, 2024)
Background: Population ageing and access to antiretroviral therapy have resulted in an increase in the proportion of older people living with human immunodeficiency virus (HIV). However, scant knowledge is available to inform the design of educational programmes to target these persons in low- and middle-income countries. Aim: This study aimed to examine how persons aged ≥ 50 years view their risk of contracting HIV, and the extent to which they are supported in preventing infection and are impacted by the HIV or acquired immune deficiency syndrome (AIDS) epidemic. Setting: Rural sites in the Western Cape Province of South Africa. Methods: This study followed a qualitative design. Two focus group discussions with persons aged ≥ 50 years and interviews with two key informants were conducted at seniors' centres. Discussions were digitally audio recorded and the recordings were transcribed, and data were thematically analysed. Results: Overall, awareness of the risk of older persons contracting HIV infection in this population was poor. Stigmatisation of the disease in the community and at health care facilities affected individuals' willingness to be tested for the virus and/or to disclose their status, if positive. Participants viewed HIV and AIDS education programmes as focussed on the youth and educational sessions for large groups were not helpful in stemming the epidemic. Conclusion: Dissemination of information on older persons' vulnerability to the disease, and education on HIV and AIDS tailored for and targeted at this age group have been relatively neglected. Contribution: Educational programmes on HIV, as well as productive channels and platforms to target older populations, particularly those with a low health literacy level are required.